Latitudinal variation of Tegula atra body size (Lesson, 1830) (Gastropod: Trochidae) in shallow waters from southern Chile - Palacios, Mauricio; Aldea Venegas, Cristian Leonardo; Corcoran, Derek (My University, 2022)
Abstract: The great variability of sea environments in Chile is associated with the length of its coastline, which is regulated by several oceanographic processes that outline the distribution, abundance, and morphology of marine species. Tegula atra is a marine gastropod greatly distributed in the southern Pacific, quality that allows it to be a good study model to evaluate the variation of its body size regarding its latitudinal distribution. A total of 236 individuals were collected in six sampling sites between 41.6° ~ 53.6°S. The relationship between weight, height (geometric mean) and its latitudinal distribution was evaluated according to Pearson and to quantile egressions. Related to the latitude, it was noted a positive and substantial correlation (Pearson) between weight and height (ρ > 0.05) moving southward. The results from the quantile regression reflected that both the slope and the R2 value are significant to the latitude with both of the analyzed variables (weight, geometric mean). Among the factors that affect the body size of the T. atra, it is suggested an adaptive differentiation of this genus to different temperatures- which has already been observed in Antarctic species. This reveals an interaction between latitude, fertility and food supply, condition that is reflected by T. atra in the Subantarctic eco-region. However, the study of intermediate areas in southern Chile and the interaction with other abiotic factors (e.g., depth) may elucidate these variations in the body size.
Keywords: body size; southern chile; latitude; tegula atra